(?m 10.6) Design study for Reserve of laser CO2 (Baghdad Science Journal, 2025)
In this paper , the CO2 laser receiver system is designed and studied, with wavelength laser 10.6 ?m in room temperature , and to evaluate the performance and discussion it via the package of optical design (ZEMAX), from its output the Spot Diagram is measured through RMS ,and from the Ray fan plot , the aberrations is found which is the normal error for the best focus named (under corrected ) , the other output was the Geometric Encircled Energy in the spot diagram . and found that the radius of spot diagram at 80% (R80%) from the total energy ,and focal shift .The designed system have high efficiency and low cost .